2022
DOI: 10.3390/ijms23126533
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phenolic Compound Production by Light Varying in Spectral Quality and Total Irradiance

Abstract: Photosynthetically active radiation (PAR) is an important environmental cue inducing the production of many secondary metabolites involved in plant oxidative stress avoidance and tolerance. To examine the complex role of PAR irradiance and specific spectral components on the accumulation of phenolic compounds (PheCs), we acclimated spring barley (Hordeum vulgare) to different spectral qualities (white, blue, green, red) at three irradiances (100, 200, 400 µmol m−2 s−1). We confirmed that blue light irradiance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…Janda et al (1996) transferred corn seedlings treated with low temperature and dark to normal temperature and light, and found that the content of plant pigment increased threefold in one day. Independently, light is also an important factor controlling anthocyanin synthesis (Mancinelli, 1983;Byrnes, 2011;Pech et al, 2022). Anthocyanin synthesis and accumulation in purple maize seedlings are the result of lightinduction (Gu et al, 2018;Shimakawa and Miyake, 2021).…”
Section: Illuminancementioning
confidence: 99%
See 1 more Smart Citation
“…Janda et al (1996) transferred corn seedlings treated with low temperature and dark to normal temperature and light, and found that the content of plant pigment increased threefold in one day. Independently, light is also an important factor controlling anthocyanin synthesis (Mancinelli, 1983;Byrnes, 2011;Pech et al, 2022). Anthocyanin synthesis and accumulation in purple maize seedlings are the result of lightinduction (Gu et al, 2018;Shimakawa and Miyake, 2021).…”
Section: Illuminancementioning
confidence: 99%
“…It is worth noting that the light absorption of anthocyanins is not only attributed to the overall ring structure and conjugated double bonds, but also depends on the light quality, luminous flux, and exposure time. Therefore, lighting conditions need to be optimized for their intensity, exposure time and type (Pech et al, 2022). Guo et al (2008) found that too much radiation from UV B may inhibit anthocyanin synthesis through DNA damage.…”
Section: Illuminancementioning
confidence: 99%
“…The study also found an association between increased SA levels at each growth condition and the changes in expression levels of the HvOGT1 gene, while the blue LED light irradiation could increase SA accumulation in barley sprouts by upregulating the expression levels of the OGT1 gene. Compared to ultraviolet A (UV-A) and other light sources, the blue LED light was demonstrated as the most effective light in promoting SA accumulation, and accounted for approximately 78% of the total phenolic content, which enhanced the activities of antioxidant enzyme, such as superoxide dismutase (SOD) and ascorbate peroxidase (APX) . In addition, the LED blue illumination supplemented with 0.1% boric acid could significantly upregulate the SA level in the YBL, and the in vitro application of the SA obtained from this treatment displayed a potential inhibition of total lipid content in the 3T3-L1 adipocytes and HepG2 hepatocytes cells, which are associated with fat accumulation .…”
Section: Defensive Role Of Saponarin Production Against Environmental...mentioning
confidence: 99%
“…In plants, their involvement in many abiotic stress responses including heat stress responses, low-temperature responses, drought exposure responses, carbon dioxide responses, light stress responses, or gamma radiation responses was reported [ 68 , 69 , 70 , 71 , 72 ]. Specifically in barley, miRNAs responsive to salinity stress [ 73 , 74 , 75 , 76 ], drought [ 77 , 78 , 79 , 80 , 81 ], nitrogen [ 82 ], boron [ 83 ], phosphorus [ 84 , 85 ], aluminum [ 74 , 86 , 87 ], cadmium [ 88 ], cold deacclimation [ 89 ], heat stress [ 90 ], and possibly to light [ 21 ] were identified till date. A chronological summary of the most impactful miRNA studies in barley (starting from 2010) can be found below in Table 1 .…”
Section: Mirnas In Barley Physiology and Stress Responsesmentioning
confidence: 99%
“…An additional and equally important application of barley seedlings is its use as a monocot model species (often considered as a model plant for the whole Triticeae tribe). Barley has a short cultivation period from seed planting to sampling the material (14 days) and does not require complex growth conditions which makes it a suitable species for a wide range of experiments [ 21 , 22 , 23 ]. Lastly, barley has a sequenced reference genome (cultivar Morex, NCBI ID: GCF_904849725.1) of a length of 4.27 Gbps consisting of 7 chromosomes, and circular chloroplastic DNA [ 24 ].…”
Section: Introductionmentioning
confidence: 99%